Primary Umbilical Endometriosis Presenting as Cyclic Umbilical Bleeding: A Case Report with Preoperative Dienogest Therapy - Anna Theresia Regina Ritonga; Anita Rachmawati; Dian Tjahyadi; Ruswana Anwar (Indonesian Journal of Obstetrics & Gynecology Science, 2026)
Introduction: Endometriosis is a chronic inflammatory gynecologic disease characterized by the presence of endometrial-like tissue outside of the uterus, most commonly on pelvic organs, affecting approximately 10% of women and girls of reproductive age worldwide. Umbilical endometriosis, also known as Villar’s nodule, is a rare form of endometriosis characterized by the presence of endometrial tissue in the umbilicus, with an incidence approximately 0.5% to 1% of all endometriosis cases worldwide.Case Report: A 36-year-old woman, P2A0, presented with a slowly enlarging umbilical nodule for 8 months, accompanied by pain and cyclic menstrual bleeding, with no history of abdominal surgery. Physical examination revealed a blackish-brown umbilical nodule measuring 2.5×3×1cm. A previous biopsy confirmed external endometriosis. Administration of dienogest at a dose of 2 mg/day for three months resulted in a favorable therapeutic response, as evidenced by clinical improvement and a reduction in lesion size to 1.5×1.5cm. The patient subsequently underwent surgical excision, and histopathological examination confirmed umbilical endometriosis. Dienogest therapy was continued for six months postoperatively, with no evidence of recurrence during follow-up.Conclusion: Primary umbilical endometriosis is a rare type of endometriosis and dienogest can be used as pretreatment before surgery.Endometriosis Umbilikalis Primer dengan Manifestasi Perdarahan Siklik dari Umbilikus: Laporan Kasus dengan Terapi Dienogest PreoperatifAbstrakPendahuluan: Endometriosis adalah penyakit inflamasi ginekologis kronis yang ditandai dengan jaringan mirip endometrium di luar rahim, paling sering pada organ panggul yang memengaruhi sekira10% wanita dan anak perempuan usia reproduksi di seluruh dunia. Endometriosis umbilikalis juga dikenal sebagai nodul Villar, adalah bentuk endometriosis langka yang ditandai dengan adanya jaringan endometrium di umbilikus, dengan insiden 0,5% hingga 1% dari semua kasus endometriosis di seluruh dunia.Laporan kasus: Seorang wanita berusia 36 tahun, P2A0, datang dengan nodul umbilikalis yang membesar perlahan selama 8 bulan, disertai nyeri dan perdarahan menstruasi siklik, tanpa riwayat operasi perut. Pemeriksaan fisik menunjukkan nodul umbilikalis berwarna coklat kehitaman berukuran 2,5×3×1cm. Biopsi sebelumnya mengonfirmasi endometriosis eksternal. Pemberian dienogest 2mg/hari selama tiga bulan menghasilkan respons terapi yang baik, yang ditunjukkan oleh perbaikan klinis dan penyusutan ukuran lesi menjadi 1,5×1,5 cm. Setelah itu, pasien menjalani eksisi bedah, dengan hasil histopatologi yang mengonfirmasi endometriosis umbilikalis. Terapi dienogest dilanjutkan selama enam bulan pascaoperasi, dan pada evaluasi lanjutan tidak ditemukan tanda-tanda kekambuhan.Kesimpulan: Endometriosis umbilikal primer adalah jenis endometriosis yang langka dan dienogest dapat digunakan sebagai pengobatan pendahuluan sebelum pembedahan.